Sea of greed [compact disc, unabridged]: a novel from the NUMA files - Cussler, Clive; Brown, Graham, 1969- (Cussler, Clive. NUMA files., 2018)
After an explosion in the Gulf of Mexico destroys three oil rigs trying to revive a dying field, Kurt Austin and the NUMA Special Projects Team are tapped by the President of the United States to find out what's gone wrong. The trail leads them to a brilliant billionaire in the alternative energy field. Her goal is the end of the oil age; her company has spent billions developing the worlds' most advanced fuel-cell systems. But is she an environmental hero or a rogue genetic engineer?